Bolshoi confidential secrets of the Russian ballet from the rule of the tsars to today - Morrison, Simon Alexander 1964- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2016)
A history of the Bolshoi Ballet from its dubious beginnings in 1776 to the present, exploring its political ties and importance under various Russian regimes and how it came to define both Russian culture and ballet itself
Includes bibliographical references (pages 429-479) and index
Keywords: Bolʹshoĭ teatr SSSR. / Balet / History; Gosudarstvennyj akademičeskij Bolʹšoj teatr Rossii -- Baletnaja Truppa; Geschichte 1776-2015; Ballet / Russia / History; Ballet / Soviet Union / History; Ballet companies / Russia / History; Ballet companies / Soviet Union / History; Ballet / Political aspects / Russia / History; Ballet / Political aspects / Soviet Union / History; PERFORMING ARTS / Dance / Classical & Ballet; HISTORY / Europe / Russia & the Former Soviet Union; Geschichte; Politik; Europa; Russland; Sowjetunion